P5-S3.05 A clinical practice intervention to increase chlamydial screening: sustaining the gain and translating into practice 4 years later. (10th July 2011) - Tebb, K; Shafer, M A
Abstract : Background: Chlamydia trachomatis (CT) continues to be a major public health problem among sexually active adolescent and young adult females. Although annual CT screening is recommended, actual rates remain low. System-based interventions are an effective approach to improve clinical practice including CT screening. Objective: There are two objectives: (1) To describe the sustainability of a systems-based, clinical practice improvement intervention to increase urine-based CT screening among adolescent girls (14–18 years old) during routine check-ups in a paediatric clinic setting (2) To describe and evaluate the translation of this intervention into control clinics. Methods: The study randomised 10 paediatric clinics (5 experimental, 5 control) within a large Northern California health maintenance organization (HMO). Clinics in the experimental group received a systems-based clinical practice improvement intervention (CPI) and controls received a traditional provider education intervention. The original study took place between 2000 and 2002 (Shafer et al JAMA, 2002). After the study ended, the intervention was translated to the remaining clinics including to the five controls. Data were tracked for four additional years (2003–2006). The proportion of 14–18-year-old girls who had sexual intercourse and who were screened for CT during their routine checkups was calculated using the same methodology as the original study. We assessed changes in the rate variable over time, within sites and between the intervention and control groups using linear mixed effects models with random intercepts. Results: The average screening rate in the intervention group was sustained at an average of 60% during the 4-year follow-up period (CI 0.41 to 0.79) with no significant increases over time. Prior to translation activities, the proportion screened in controls was 21%. After translation activities, the control group exhibited statistically significant linear and quadratic effects of time (p=0.0019 by Wald χ 2 test). The estimated rate for the controls was 0.42 (95% CI 0.25 to 0.59) at time 1, increased to a maximum of 0.69 (95% CI 0.55 to 0.83) at year 2.5, then declined to 0.52 (95% CI 0.35 to 0.70) at the end of year 4. Conclusions: This CPI systems intervention was both translatable and sustainable to other paediatric clinics within this HMO.